1985
DOI: 10.1136/bmj.291.6487.17
|View full text |Cite
|
Sign up to set email alerts
|

Deaths from rhesus haemolytic disease in England and Wales in 1982 and 1983.

Abstract: Examination of death certificates and the clinical notes of the patients concerned showed that the number of deaths from rhesus (D) haemolytic disease in England and Wales was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Although the number of affected pregnancies in this survey was small, it compares reasonably with other studies. Leggat et al found 16 affected pregnancies, over a much longer period 6 and Bowman et al 2 studying 31 affected pregnancies presenting over 47 years, from 1944–1990. Our study, although including a relatively large number of Kell pregnancies, suffers from the weakness that practice and practitioners will have altered over the thirteen year period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the number of affected pregnancies in this survey was small, it compares reasonably with other studies. Leggat et al found 16 affected pregnancies, over a much longer period 6 and Bowman et al 2 studying 31 affected pregnancies presenting over 47 years, from 1944–1990. Our study, although including a relatively large number of Kell pregnancies, suffers from the weakness that practice and practitioners will have altered over the thirteen year period.…”
Section: Discussionmentioning
confidence: 99%
“…This often results in prolonged intensive neonatal care and sometimes culminates in perinatal death. The incidence of anti‐D sensitisation has decreased due to the administration of anti‐D immunoglobulin, while the importance of other antibodies has increased 1,2 . Anti‐Kell antibodies appear to cause significant suppression of erythropoiesis rather than red cell destruction 3,4 and, unlike Rhesus disease, the outcome is not affected by previous obstetric history 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Haemolytic disease of the newborn (HDN) is an isoimmune haemolytic jaundice which prior to modern interventions had a perinatal mortality rate of 50% that has now decreased to 7 per 100 000 births 1. The mainstay of treatment is intensive phototherapy with exchange transfusion recommended if, in spite of phototherapy, the total serum bilirubin (TSB) approaches a level considered to cause a risk of bilirubin encephalopathy 2.…”
Section: Commentarymentioning
confidence: 99%
“…However, the immune response leading to sensitization in Rh-ve mother is much less. Incidence of antepartum sensitization is 1-2 %, and of postpartum sensitization, it is only 10-15 % of women having Rh?ve babies [1]. The discovery, introduction, and utilization of Rh-D immunoglobulin (anti-D) for prophylaxis against Rh immunization is one of the major medical achievements and successful application of preventive obstetric medicine in the last century.…”
Section: Introductionmentioning
confidence: 99%